Cognitive processes of ingroup favoritism across 20 countries: An eye-tracking investigation of culture, behavior, and cognition - Rima-Maria Rahal; Frederik Schulze Spüntrup (Proceedings of the National Academy of Sciences, 2025)
Whether and to what degree culture modifies cognition has been an area of research often limited by possibilities to gather relevant data across societies. In this project, we leverage webcam-based eye-tracking to study cultural variations of cognitive processes underlying in-group favoritism. Participants (n = 1850, k = 20) are assigned to an in-group based on a color perception task, complete a group reinforcement stage, and then make decisions to allocate points between themselves and random matched players in a repeated decomposed dictator game, facing either an in- or an out-group member. During this task, we recorded eye-gaze with participants’ webcams. Results show substantial variation in behavioral in-group favoritism across cultures, linking discrimination based on group membership to higher societal uncertainty. Individual preferences for prosociality conditioned differences in visual search effort, but the directionality of the effect differs between countries. Individual-level predictors explained participants remaining colorblind toward others’ group membership, where society-level predictors did not. Overall, we demonstrate the importance of taking culture into account when assessing cognitive processes underlying behavior. Implications for globally oriented policymaking to reduce discrimination are discussed.